Från kallt till varmt - norsk oceanografisk forskning i Weddelhavet, Antarktis - Darelius, Elin Maria K; Foldvik, Arne (Det norske videnskaps-akademi, 2020)
Keywords: Sørishavet; Weddellhavet; oseanografi

C.A. Larsen : explorer, whaler & family man - Riffenburgh, Beau (Red.); Kløver, Geir O (Red.) (The Fram Museum, 2016)
Keywords: Antarctic ekspedisjonen; Antarktis; Carl Anton Larsen; D/S Antarctic; D/S Jason; Jason ekspedisjonene; Weddellhavet; hvalfangere; hvalfangst; oppdagelsesreiser; polarforskning

Effects of hydrographic variability on the spatial, seasonal and diel diving patterns of southern elephant seals in the eastern Weddell Sea - Biuw, Martin; Nøst, Ole Anders; Stien, Audun; Zhou, Qianhe; Lydersen, Christian; Kovacs, Kit M (PloS One, 2010)
Weddell Sea hydrography and circulation is driven by influx of Circumpolar Deep Water (CDW) from the Antarctic Circumpolar Current (ACC) at its eastern margin. Entrainment and upwelling of this high-nutrient, oxygen-depleted water mass within the Weddell Gyre also supports the mesopelagic ecosystem within the gyre and the rich benthic community along the Antarctic shelf. We used Conductivity-Temperature-Depth Satellite Relay Data Loggers (CTD-SRDLs) to examine the importance of hydrographic variability, ice cover and season on the movements and diving behavior of southern elephant seals in the eastern Weddell Sea region during their overwinter feeding trips from Bouvetøya. We developed a model describing diving depth as a function of local time of day to account for diel variation in diving behavior. Seals feeding in pelagic ice-free waters during the summer months displayed clear diel variation, with daytime dives reaching 500-1500 m and night-time targeting of the subsurface temperature and salinity maxima characteristic of CDW around 150-300 meters. This pattern was especially clear in the Weddell Cold and Warm Regimes within the gyre, occurred in the ACC, but was absent at the Dronning Maud Land shelf region where seals fed benthically. Diel variation was almost absent in pelagic feeding areas covered by winter sea ice, where seals targeted deep layers around 500-700 meters. Thus, elephant seals appear to switch between feeding strategies when moving between oceanic regimes or in response to seasonal environmental conditions. While they are on the shelf, they exploit the locally-rich benthic ecosystem, while diel patterns in pelagic waters in summer are probably a response to strong vertical migration patterns within the copepod-based pelagic food web. Behavioral flexibility that permits such switching between different feeding strategies may have important consequences regarding the potential for southern elephant seals to adapt to variability or systematic changes in their environment resulting from climate change.
Keywords: Bouvetøya; Sørishavet; Weddellhavet; hydrografi; klimaendringer; marin biologi; oseanografi; seler; sjøpattedyr

Klimavariasjoner gjennom de siste 45 000 14C år i Weddellhavet, Antarktis - Larsen, Anne Marit Løland (Universitetet i Bergen, 2001)
Keywords: Sørishavet; Weddellhavet; maringeologi; paleoklimatologi; sedimenter